Public policy design and implementation in Slovenia - Mencinger, Jernej (Mednarodna revija za javno upravo, 2017)
Public policy design and implementation is a complex process, and so decision makers try to monitor all of the policy lifecycle stages in a particular policy domain. However, the question of coherent integration of various policy activities arises, including agenda-setting, ex-ante evaluation, formulation, decision-making, implementation, ex-post evaluation of individual policies, sector-specific ones, and even horizontal ones. Therefore, it is important to investigate and understand the reasons why an individual country, such as Slovenia, does not exploit all potential aspects of carrying out policy activities in a systematic and coherent manner. This article explores and analyzes Slovenian practice in policy design based on an in-depth empirical study among key public policyholders and decision makers. Furthermore, the authors identify the key success factors that facilitate or inhibit the development and progress of public policies, programs, and projects (PPPP) in Slovenia. The key findings indicate a particular lack of a professional policy unit to monitor the process holistically and the absence of ex-post evaluation. A need for a systemic solution in public policy design is established, which would merge different authorities' efforts, epistemic communities, and the public in developing a structural multilevel model for good public governance.
Keywords: javna uprava; javne politike; public administration; public policy; Slovenia; Slovenija; upravljanje